A Retrospective Clinical Analysis of the Serum Bile Acid Alteration Caused by Traumatic Brain Injury - Zhu, Yuanrun; Chen, Zijian; You, Wendong; Wang, Yadong; Tu, Mengdi; Zheng, Peidong; Wen, Liang; Yang, Xiaofeng (Frontiers in Neurology, 2021)
Traumatic brain injury (TBI) can cause damage to peripheral organ system such as digestive organ system and alterations of gut microbiota in addition to brain injury. Our previous study found that TBI induced gastrointestinal dysfunction accompanied by alterations of bile acid metabolism. Bile acid and its receptors have been reported to play important roles in various neurological diseases. To further examine the changes of bile acid metabolism in TBI patients, we performed a retrospective clinical analysis. In this study, 177 patients were included, and the results showed that TBI patients had more frequent antibiotic use compared with control group. Regression analysis identified TBI as independent factor for reduction of serum bile acid level (B=-1.762, P=0.006), even with antibiotic use taken into regression model. Sub-group regression analysis of TBI patients showed that antibiotic use was negatively associated with bile acid level, while creatinine and triglyceride were positively associated with bile acid level. In conclusion, these data indicated that TBI could greatly reduce serum bile acid. This study provided preliminary but novel clinical evidence of TBI interfering with bile acid metabolism, and further studies with large sample sizes are needed to validate these findings in the future.